1984
DOI: 10.1002/ps.2780150614
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulated rain on deposits of some cotton pesticides

Abstract: Commercially grown cotton and potted cotton plants were sprayed with five pesticides, and simulated rain was applied 1–72 h later. Leaf samples were analysed to determine the effect of the rain on the original deposits. It was found that 2 to 5 mm of simulated rain applied 1 h after spraying, washed off 50% or more of the original deposit. An increase in rainfastness of the pesticides occurred over a period of time after spraying. The type of formulation seemed to affect rainfastness, but the origin of a formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…In contrast, the fractions of toxaphene and fenvalerate washed from the plants were relatively constant at 10 and 7%, respectively, regardless of time after application and amount on the plants. Pick et al (1984), using overhead irrigation to simulate rair~fall, concluded that endosulfan, cypermethrin, and carbaryl became more resistant to washoff with time after application. Even low amounts of rain can have drastic effects on insecticide residues.…”
mentioning
confidence: 99%
“…In contrast, the fractions of toxaphene and fenvalerate washed from the plants were relatively constant at 10 and 7%, respectively, regardless of time after application and amount on the plants. Pick et al (1984), using overhead irrigation to simulate rair~fall, concluded that endosulfan, cypermethrin, and carbaryl became more resistant to washoff with time after application. Even low amounts of rain can have drastic effects on insecticide residues.…”
mentioning
confidence: 99%
“…However, significant differences were only observed 48 hours after application (Table 2). In a previous study, Pick et al (1984) observed that 50% of the applied insecticide was removed after 5 mm of precipitation occurred 1 hour after insecticide application. Moreover, the authors concluded that the interval between insecticide application and the occurrence of rain should be increased as the volume of precipitation increases.…”
Section: Resultsmentioning
confidence: 96%
“…Among the components of the production costs, the pest control represents approximately 50% of the cost with pesticides in the main areas that produce cotton in Brazil (RICHETTI et al, 2005), which demands discerning analysis for employment of pests chemical control. Among the main pests are the cotton aphids (Aphis gossypii) that demand a lot of control interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations